The individual and the reality in Czesław Miłosz and Witold Gombrowicz - Kulas, Piotr (Folia Philosophica, 2009)
The aim of this paper is to discuss Czesław Miłosz’s and Witold Gombrowicz’ views on the role of individual, its relationship with reality and the others. Both authors can be seen as adversaries in the debate (one of the most important in the XXth-century humanities) between the individual agency and the involvement in the community. The debate concerned mostly the consequences of the philosophy of the self (mostly in phenomenology and existentialism). Fascinated with phenomenology and existentialism, Gombrowicz argued that they are an important turn in the Western thought, for it is thanks to them that the human condition might be described in the most adequate way so far. He followed partisans of phenomenology in their conviction according to which it is the individual that constitutes reality as the world is given to the individual for interpretation, so it is the individual that makes sense of its surrounding. Conversely, Czesław Miłosz rather dissociated himself from this kind of beliefs, mainly while being involved in the debate with Gombrowicz. He pointed flows in Gombrowicz’ convictions and its consequences derived from the acceptance of the point of view which, in his opinion, leads to radical subjectivism and breaking of the inter-personal relations.